زواج الصغار وأثر التغيرات الاجتماعية عليه - Basri, Ibrahim; Mohamed Fathy, Mohamed Abdelgelil; Dahmah Khaled Ali, Ali (2018)
Marriage is an important stage in human life because it has a direct influence on the individual, family and society. Therefore, the age of marriage is of great importance. The purpose of this article is to reveal the most significant negative and positive influences of early marriage, and highlight the notion of social changes in relation to early marriage through knowledge of the age of marriage, taking into account the conditions of contemporary life. The researcher focused on the knowledge of early marriage and its negative and positive influences. In this article, the researcher adopted inductive and deductive methods. Among the most important findings of this study is that the Islamic law paid great attention to marriage in order to protect youth from any deviation and to protect societies from corruption. Marriage is a life contract that has been considered to be influenced with time, perhaps due to money despotism, loss of values, and intentions. Early marriage pays a significant role in social changes, both negatively and positively.